Environmental Assessment of Recyclable Waste Valorization in United Arab Emirates. Issue 1 (November 2021) - Elfeky, A; Abdallah, M; Fattah, K
Abstract: The United Arab Emirates (UAE) has one of the largest per capita carbon footprints and solid waste generation rates in the world. In preparation for the post-oil future, the UAE has planned to diversify its energy mix with renewable sources. Waste valorization, particularly material and energy recovery (MER), presents a promising solution for the waste and energy challenges of the future. It is thus of great importance to ensure that the shift to MER systems lead to a concomitant positive impact on the environment. This research aims to assess the environmental impacts of selected waste management strategies incorporating MER systems in the UAE. The study is focused on the valorization of recyclable wastes through incinerators and/or material recovery facilities (MRFs) compared to existing landfill practices. The mass burn strategy increased the energy produced by 88% compared to the combined MER strategy due to the high energy yield of recyclables. It was found that combining energy and material recovery was the optimum environmental option in terms of global warming and abiotic depletion. The mass burn strategy had a favourable positive impact on freshwater aquatic ecotoxicity and human toxicity, yet it resulted in the highest acidification potential (ACP) and eutrophication potential (ETP). On the other hand, the MRF strategy achieved positive ACP and ETP impacts. Overall, all MER-based strategies achieved better environmental performance compared to existing landfilling practices